ADOPTION OF THE MOBILE PAYMENT SYSTEM IN SMALL MEDIUM-SIZED ENTERPRISES - Dilarbo, Pertiwi Aisyah; Astuti, Endang Siti (PROFIT: JURNAL ADMINISTRASI BISNIS, 2020)
The purpose of this study is to present a conceptual model between Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition, Behavioral Intention and Actual Usage. Based on theoretical and empirical study about Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition, Behavioral Intention and Actual Usage, this study explain the constructs and the proposition that are used as a basis in constructing conceptual models. Based on previous studies, the authors develop a proposition where a Mobile Payment service will be more likely to adopt by the Mobile Payment service. Thus, further studies are expected to discuss the variables in this study, as well as develop estimates of other variables that can influence or increase by the variables that have been discussed.